2022
DOI: 10.1002/jcp.30779
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to type 3 diabetes mechanism: The interplay between noncoding RNAs and insulin signaling pathway in Alzheimer's disease

Abstract: Today, growing evidence indicates that patients with type 2 diabetes (T2D) are at a higher risk of developing Alzheimer's disease (AD). Indeed, AD as one of the main causes of dementia in people aged more than 65 years can be aggravated by insulin resistance (IR) and other metabolic risk factors related to T2D which are also linked to the function of the brain. Remarkably, a new term called “type 3 diabetes” has been suggested for those people who are diagnosed with AD while also showing the symptoms of IR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 218 publications
0
6
0
Order By: Relevance
“…DM is the most common metabolic disorder and the direct cause of its occurrence is usually due to defective insulin action or insufficient insulin secretion ( 20 , 21 ). Several real-world clinical cases suggest that brain-related mild cognitive impairment complications in diabetes may lead to cognitive deficits, which gradually develops into AD ( 22 , 23 ).…”
Section: Metabolic Diseases and Admentioning
confidence: 99%
“…DM is the most common metabolic disorder and the direct cause of its occurrence is usually due to defective insulin action or insufficient insulin secretion ( 20 , 21 ). Several real-world clinical cases suggest that brain-related mild cognitive impairment complications in diabetes may lead to cognitive deficits, which gradually develops into AD ( 22 , 23 ).…”
Section: Metabolic Diseases and Admentioning
confidence: 99%
“…In addition, it is reported that the dysregulation of β‐site amyloid precursor protein cleaving enzyme 1 (BACE1), a key gene involved in the production of Aβ in the brain, can lead to both AD‐like symptoms and the development of diabetic complications 25 . Thus, AD is sometimes referred to as diabetes type 3 26,27 …”
Section: Introductionmentioning
confidence: 99%
“…25 Thus, AD is sometimes referred to as diabetes type 3. 26,27 In recent years, there is a growing interest in repositioning existing antidiabetic drugs for other diseases, and a few of them have shown great potential for treating cancer, neurodegenerative diseases, or cardiovascular diseases. 28 Considering the close connection between AD and T2D, using medications that are already used to for diabetes to treat AD has drawn much attention.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes and dementia are often comorbid in ageing individuals, 10 thus a link between the two conditions is implied. Of note, insulin resistance in the brain has been referred to as ‘type 3 diabetes’, and is considered a major driving force in the pathophysiology of AD 11,12 …”
Section: Introductionmentioning
confidence: 99%
“…Of note, insulin resistance in the brain has been referred to as 'type 3 diabetes', and is considered a major driving force in the pathophysiology of AD. 11,12 Over the last several decades, diabetes has become an established risk factor for cognitive decline and dementia, yet the extent to which each subtype of dementia (notably AD and VaD) is implicated remains controversial, and the impact of treatment remains uncertain. 5,13,14 We therefore aimed to conduct a systematic umbrella review of the evidence linking diabetes and its treatment to risk of dementia, as well as an updated meta-analysis on the association between antidiabetic treatment and incident dementia.…”
Section: Introductionmentioning
confidence: 99%